Hemodynamic implications of mitral annular calcification in patients undergoing transcatheter aortic valve implantation for severe aortic stenosis - Hirasawa Kensuke; Butcher Steele C; Pereira Ana Rita; Meucci Maria Chiara; Stassen Jan; van Rosendael Philippe; Marsan Nina Ajmone; Bax Jeroen J; Delgado Victoria (Springer Dordrecht, 2025)
Purposes
Predicting hemodynamic changes of stenotic mitral valve (MV) lesions with mitral annular calcification (MAC) following transcatheter aortic valve implantation (TAVI) may inform clinical decision-making. This study aimed to investigate the association between the MAC severity quantified by computed tomography (CT) and changes in mean transmitral gradient (mTMG), mitral valve area (MVA) and stroke volume index (SVi) following TAVI.
Methods and results
A total of 708 patients (median age 81, 52% male) with severe aortic stenosis (AS) underwent pre-procedural CT and pre- and post-TAVI transthoracic echocardiography. According to the classification of MAC severity determined by CT, 299 (42.2%) patients had no MAC, 229 (32.3%) mild MAC, 102 (14.4%) moderate MAC, and 78 (11.0%) severe MAC. After adjusting for age and sex, there was no significant change in mTMG following TAVI (Delta mTMG = 0.07 mmHg, 95% CI -0.10 to 0.23, P = 0.92) for patients with no MAC. In contrast, patients with mild MAC (Delta mTMG = 0.21 mmHg, 95% CI 0.01 to 0.40, P = 0.018), moderate MAC (Delta mTMG = 0.31 mmHg, 95% CI 0.02 to 0.60, P = 0.019) and severe MAC (Delta mTMG = 0.43 mmHg, 95% CI 0.10 to 0.76, P = 0.0012) had significant increases in mTMG following TAVI, with greater changes associated with increasing MAC severity. In contrast, there was no significant change in MVA or SVi following TAVI.
Conclusion
​​​​​​​In patients with severe AS undergoing TAVI, MAC severity was associated with greater increases in post-procedural mTMG whereas MVA or SVi remained unchanged. MAC severity should be considered for potential subsequent MV interventions if TAVI does not improve symptoms.